Evolução Tectono-Estratigráfica e Paleoclimática da Formação Maricá (Escudo Sul-Rio-Grandense, Brasil): um Exercício de Geologia Histórica e Análise Integrada de uma Bacia Sedimentar Neoproterozóica - DE BORBA, ANDRÉ WEISSHEIMER; MARASCHIN, ANDERSON JOSÉ; MIZUSAKI, ANA MARIA PIMENTEL (Pesquisas em Geociências, 2007)
Significant improvement in the knowledge concerning the Neoproterozoic Maricá Formation of the Sul-riograndense Shield, southern Brazil, was obtained in the latest years. This contribution synthesizes recent data obtained though an integrated analysis of the lowermost unit of the “Camaquã Basin”. Stratigraphic and paleocurrent analyses, petrography, Sr and Nd isotope geology, U-Pb SHRIMP geochronology and Ar-Ar dating were applied to the sedimentary and volcanogenic record of the Maricá Formation in order to better constrain its depositional evolution. The Maricá Formation was deposited within a coastal to shallow marine setting, its detrital load being derived from the weathering of granite-gneissic, paleoproterozoic (1.76 to 2.37 Ga) source rocks, possibly located in the western La Plata craton. A syn-depositional, partially explosive, volcanic event was recognized and dated by U-Pb SHRIMP at 630.2 ± 3.4 Ma, positioning the inception of the “Camaquã Basin” at the end of the Cryogenian. Thus, the deposition of the Maricá Formation post-dates the global-scale Marinoan glaciation (660-635 Ma), possibly recording greenhouse paleoclimatic conditions. Field, petrographic and isotopic evidence supports this interpretation. The evolution of the Maricá Formation started during the collisional climax of the Brasiliano II orogenic system (Dom Feliciano orogen), thus the analyzed sedimentation could represent the infilling of a foreland basin. It is possible that correlative portions of the foreland system may be preserved in other sedimentary or metamorphic successions of the Mantiqueira Province, such as the Fuente del Puma (Lavalleja), Porongos, Brusque, Abapã (Itaiacoca), Cerro da Árvore and Passo da Capela units. The 507.3 ± 1.8 and 506.7 ± 1.4 Ma Ar-Ar step-heating ages obtained in K-feldspars from volcanogenic samples of the Maricá Formation are most likely associated with uplift and cooling below ca. 200ºC, possibly during the inception of the rift where the Camaquã Group (Santa Bárbara and Guaritas formations) accumulated.